Reconcilling migrants' well-being and the public interest - Welfare state, firms and citizenship in transition = Concilier bien-être des migrants et intérêt collectif - Etat social, entreprises et citoyenneté en transformation - Council of Europe (Strasbourg, 2007)
"This volume has two purposes. First, it looks at why migrant welfare is not always acknowledged as forming part of the general well-being of host countries. And second, by suggesting alternative approaches, it sets out to help bring about a “just, multicultural society”, in which rights and mobility are realities for everyone. The radical changes currently under way in the welfare state, in private enterprise and in the various manifestations of citizenship are a perfect starting point for showing that the rights of migrants and nationals, far from being in competition, actually reinforce each other. While rejecting the essentialisation of “diversities”, the authors call for greater cultural accommodation in all walks of life – in institutions and businesses, social services and hospitals, families and associations – to better meet the needs of multicultural societies."